Paraguay : Report on the Observance of Standards and Codes (ROSC)-Data Module Volume I. (IMF Staff Country Reports; Country Report, 2014)
OVERALL ASSESSMENT This Report on the Observance of Standards and Codes (ROSC)-Data Module provides an update of the assessment conducted in February 2006, which was based on the July 2003 version of the IMF's Data Quality Assessment Framework (DQAF). This ROSC Data Module is the first complete report based on the May 2012 vintage of the DQAF that covers six datasets, namely, national accounts (NA), consumer price index (CPI), producer price index (PPI), government finance statistics (GFS) and public sector debt statistics, monetary statistics, and balance of payments (BOP) and international investment position (IIP) statistics. The agencies that compile and disseminate these statistics are the Central Bank of Paraguay (CBP) for all datasets but GFS, which are compiled and disseminated by the Ministry of Finance (MOF). Following the 2006 ROSC Data Module mission, Paraguay made significant improvements in the compilation and dissemination of macroeconomic statistics, including (i) adequate methodological treatment of the two large binational hydroelectrical enterprises to properly reflect their contribution to Paraguay's GDP, BOP, and other international accounts; (ii) compilation and dissemination of quarterly national accounts and integrated economic accounts for the total economy up to net lending; (iii) new CPI series (December 2007=100) and PPI series (June 2011=100), with several methodological improvements (introduction of an adequate treatment of seasonal products and use of improved estimation techniques for missing prices), among others. Paraguay participates in the General Data Dissemination System (GDDS) since September 2001, and the metadata for its macroeconomic statistics are posted on the IMF's Dissemination Standards Bulletin Board (DSBB). Paraguay meets GDDS recommendations for the coverage, periodicity, and timeliness of data, with the following two exceptions: (i) in the financial sector, the depository corporations (DC) survey is compiled on a monthly basis with a one-month lag but is not disseminated; and (ii) in the external sector, the debt service payment schedules for both public and private external debt are not disseminated. Appendix I provides an overview of Paraguay's dissemination practices compared to the GDDS. At the request of the authorities, Paraguay's current data dissemination practices were also reviewed against the requirements of the Special Data Dissemination Standard (SDDS). A detailed description of Paraguay current practices against the SDDS is presented in Appendix IV of the accompanying detailed assessment document (Volume III).